2021
DOI: 10.3389/fpls.2021.631239
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Wide Analysis of Heat-Stress in Pinus radiata Somatic Embryos Reveals a Combined Response of Sugar Metabolism and Translational Regulation Mechanisms

Abstract: Somatic embryogenesis is the process by which bipolar structures with no vascular connection with the surrounding tissue are formed from a single or a group of vegetative cells, and in conifers it can be divided into five different steps: initiation, proliferation, maturation, germination and acclimatization. Somatic embryogenesis has long been used as a model to study the mechanisms regulating stress response in plants, and recent research carried out in our laboratory has demonstrated that high temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 76 publications
6
23
0
Order By: Relevance
“…The chromatographic separation was performed on a Triart C18 Capillary Column 1/32” (12 nm, S-3µm, 150 × 0.3 mm, YMC) and using a Triart C18 Capillary Guard Column (0.5 × 5 mm, 3 μm, 12nm, YMC). Further details of the LC methodology (mobile phases, flow rate etc) and the different mass spectrometer operation modes used for DDA and DIA experiments are resumed in Castander-Olarieta et al (2021a). The only differences are the following: LC program [5 – 30% of B (0 - 50 min), 30 – 98% of B (50 – 52 min), 98% of B (52-54 min), 98 - 5% of B (54 – 56min), and 5% of B (56 – 65 min], voltage of the ionization source (5500 V), nebulizer gas 1 (GS1) and gas 2 (GS2) pressures (25 and 10 psi respectively), candidate ions minimum count threshold (100) and mass spectrometer software version (Analyst® TF 1.8.1, Sciex®).…”
Section: Methodsmentioning
confidence: 99%
“…The chromatographic separation was performed on a Triart C18 Capillary Column 1/32” (12 nm, S-3µm, 150 × 0.3 mm, YMC) and using a Triart C18 Capillary Guard Column (0.5 × 5 mm, 3 μm, 12nm, YMC). Further details of the LC methodology (mobile phases, flow rate etc) and the different mass spectrometer operation modes used for DDA and DIA experiments are resumed in Castander-Olarieta et al (2021a). The only differences are the following: LC program [5 – 30% of B (0 - 50 min), 30 – 98% of B (50 – 52 min), 98% of B (52-54 min), 98 - 5% of B (54 – 56min), and 5% of B (56 – 65 min], voltage of the ionization source (5500 V), nebulizer gas 1 (GS1) and gas 2 (GS2) pressures (25 and 10 psi respectively), candidate ions minimum count threshold (100) and mass spectrometer software version (Analyst® TF 1.8.1, Sciex®).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Touraev et al (1996) observed an increased number of tobacco somatic embryos from shoot tips following the imposition of high temperatures, ranging from 33 • C to 37 • C [80]. Recently, Castander-Olarieta et al (2021) reported that the exposure of Pinus radiata explants to 60 • C for 5 min significantly promotes embryogenic competence [81]. These effects were associated with an elevated abundance of proteins involved in the post-transcriptional regulation (ARGONAUTE 1D), as well as biosynthesis of fatty acids, sugars, and cell wall carbohydrates.…”
Section: Temperature Stressmentioning
confidence: 95%
“…Programmed cell death (PCD) is a conserved process occurring during plant embryogenesis, which is responsible for the dismantling of the suspensor and the removal of subordinate embryos in gymnosperm seeds [81,82]. During in vitro embryogenesis PCD eliminates specific embryogenic cells [83], and it is required for shaping the embryo body, as unequivocally demonstrated in spruce [84].…”
Section: Programmed Cell Death (Pcd) During Sementioning
confidence: 99%
“…Later, proteomics studies during partial desiccation of Picea asperata somatic embryos showed that stress-related proteins associated with osmosis, PGR metabolism, antioxidative proteins, defense proteins, and photosynthesis-related proteins were critical factors for improving the maturation and germination of somatic embryos [82]. Besides, high-temperature application during the initiation of embryonal masses of Pinus radiata exhibited improvement in the generation of the number of somatic embryos, which was associated with the over-accumulation of stress-related proteins and enzymes connected to the synthesis of fatty acids, myo-inositol, and cell-wall [83].…”
Section: Gymnospermsmentioning
confidence: 99%